PENGARUH JUMLAH PENDUDUK DAN PERKEMBANGAN TEKNOLOGI TERHADAP PERTUMBUHAN EKONOMI DI DKI JAKARTA PADA MASA COVID-19 - Anisa Fadhilatus Sholikhah; Yunaita Rahmawati (Investama : Jurnal Ekonomi dan Bisnis, 2022)
Economic growth is one of the parameters for creating people's welfare, so economic growth becomes one of the benchmarks in assessing the economy of a region. But in this study, there is a discrepancy related to population and technological developments and economic growth. This discrepancy is found in the population data and technological developments, which have continued to increase in the same year in the DKI Jakarta Province area, but in the economic growth data, it has actually decreased. This study aims to analyze the influence of population and technological developments on economic growth in the DKI Jakarta area during the Covid-19 period. The design of this research is quantitative, with the causal-associative method used and data processing using panel data regression. The data collection method used is the document method, namely by intermediary existing records, with data variables Y economic growth, X1 population, and X2 technological developments. The results of the analysis in this study state that the partial population has a negative effect on economic growth, while technological developments have a positive effect on economic growth. simultaneously, population and technological developments affect economic growth by 85.7%